Ion doping method based on first principle calculation and application thereof
Through the ion doping method based on the first principle, the ore phase structure of cement clinker is optimized, and the problems of unstable cement strength and durability and low resource utilization efficiency are solved, and the cement performance is significantly improved and the resource utilization is efficient.
Patent Information
- Application Number
- CN202411667212.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
AI Technical Summary
The existing cement production methods have shortcomings in mineral phase stability, resource utilization efficiency and performance optimization, resulting in unstable cement strength and durability, and increased resource waste and energy consumption.
Using the ion doping method based on the first principle, the crystal structure model of the cement clinker ore phase is constructed, structural relaxation and static self-consistent calculations are performed, the optimal doping elements, location and concentration are determined, and the activity and strength of the multi-orch phase structure are optimized.
It significantly improves the physical and chemical properties of cement, improves compressive strength, durability and chemical corrosion resistance, improves resource utilization efficiency, and promotes the accuracy and sustainable development of cement design.
Smart Images

Figure CN119580868A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to activity enhancement of a multi-ion doped mineral phase structure and application thereof in cement. Background Art
[0002] In the construction industry, cement is an important basic material, and its performance directly affects the strength and durability of concrete. Cement clinker is one of the raw materials for preparing cement, and its main components are multi-mineral phase structures such as calcium silicate minerals (such as C3S and C2S). Studies have found that ion doping technology can significantly improve the performance of cement clinker. It is one of the most commonly used and effective methods and has broad application prospects in the cement industry. However, the current traditional doping methods only focus on the doping effects of individual mineral phases and lack systematic theoretical support and calculation basis, which mainly leads to the following problems:
[0003] 1. Poor relative stability of mineral phase:
[0004] Due to changes in environmental and production conditions, there are large differences in the distribution of different mineral phases in cement and their physical stability, which directly affects the hydration rate and final strength of cement. In traditional methods, if the proportion of mineral admixtures (such as fly ash, slag, etc.) is too high, the main mineral phase (such as calcium aluminate phase) in the clinker will be unstable, which will affect the strength and durability of cement. For example, in some cases, the use of phosphates can improve certain properties of cement, but excessive and uneven doping will affect the formation of C3A, resulting in unstable mineral phases in cement during hydration.
[0005] 2. Low efficiency of resource utilization:
[0006] The current cement production method has low utilization efficiency of mineral raw materials. For example, the main components of the raw materials (such as limestone, clay, etc.) have composition changes or the impurity content is too high, resulting in a decrease in the utilization efficiency of raw materials during the production process; during the calcination process, too low a temperature may cause the mineral phase to fail to react completely, while too high a temperature may cause the loss of some valuable components, reducing the utilization efficiency of raw materials. All these will cause waste of resources and increase energy consumption, restricting the realization of sustainable development.
[0007] 3. Limited performance optimization methods:
[0008] Although there are many methods to improve cement performance based on admixtures (such as slag, fly ash, etc.), these methods can often only optimize a certain mineral phase and lack systematicity and pertinence. For example, fly ash is usually used to improve the compressive strength and durability of cement, especially for the hydration of C3S (tricalcium silicate) phase in cement. However, if excessive fly ash is added to cement, due to its high loss on ignition, the relative proportion of C3S phase may be reduced, which in turn affects the strength of cement. This optimization method is more targeted at the C3S phase, while the impact on other mineral phases (such as C2S) has not been effectively considered.
[0009] With the development of computers and the improvement of their working performance, computational materials science has emerged rapidly, driving the transformation of materials research and development from the "experience + trial and error" model to a computationally driven research and development model, introducing a scientific data-driven + computer learning research paradigm, and significantly accelerating the exploration of materials research problems.
[0010] Therefore, how to reveal the structural changes and energy state changes of mineral phases during ion doping at a microscopic level, and thereby promote the accuracy of cement design, has become a technical problem that needs to be urgently solved in this field. Summary of the invention
[0011] In response to the above problems, the present invention provides an ion doping method based on first principles calculation to determine the phase change behavior and electronic structure regulation caused by different doping elements at the microstructural level, thereby improving the physical and chemical properties of cement.
[0012] The technical solution of the present invention is:
[0013] An ion doping method based on first principle calculation comprises the following steps:
[0014] Step 1: construct a cement clinker mineral phase crystal structure model, and perform structural relaxation on the model to obtain a stable model crystal structure;
[0015] Step 2: Based on the structural relaxation, the static self-consistent calculation is started by adjusting the two parameters in the VASP calculation input file INCAR, inputting the initial density ρ0(r) of the clinker crystal, calculating its effective potential Veff(r) and solving the Kohn-Sham equation, and finally comparing the convergence to obtain a stable crystal structure;
[0016] Step 3: After the static self-consistent calculation forms a stable crystal structure:
[0017] Step 3.1, calculate the formation energy Ef of atomic substitution in cement clinker, use ions to replace different atoms in the clinker, first replace atoms at different positions to represent the doping position, and then replace different numbers of atoms from small to large to represent the doping concentration, and obtain the effective formation energy;
[0018] Step 3.2, calculate the electronic properties by calculating the bond length-bond order, state density and charge density;
[0019] Step 4: Based on the formation energy obtained in 3.1 and the electronic property parameters obtained in 3.2 in step 3, the existence state, doping preference and site of different elements doped in each of the cement clinker mineral phase crystals are compared to obtain the best doping measure.
[0020] Specifically, the cement clinker mineral phase in step 1 includes:
[0021] Tricalcium silicate (C3S), dicalcium silicate (C2S), calcium silicate (CS), calciteite (C3S2), tricalcium aluminate (C3A), monocalcium aluminate (CA), monocalcium dialuminate (CA2), dodecaaluminate (C 12 A7), dicalcium ferrite (C2F), tetracalcium aluminoferrate (C4AF), hexacalcium aluminoferrate (C6AF2), hexacalcium ferroaluminate (C6A2F), calcium sulfoaluminate (C4A3$), calcium sulfosilicate (C5S2$), calcium barium sulfoaluminate (C3A3$·BaO), calcium strontium aluminate (C3A3$·SrO), calcium fluoroaluminate (C 11 A7·CaF2), calcium chloroaluminate (C 11 A7·CaC12), tricalcium phosphate (C3P), tetracalcium phosphate (C4P), calcium aluminophosphate (C8A4P), P phase (C6A4FS), Q phase (Ca 20 Al 32 -2nMgnSinO 68 ), grosvenite (C2AS) and / or alinite (Ca 22 Si6Al2C12O 36 ).
[0022] Specifically, the crystal structure described in step 1 includes: formation energy, bond length and bond order distribution, electronic structure, space group, number of non-bonding electrons, effective charge, local charge density, interplanar spacing and unit cell parameters.
[0023] Specifically, the steps of constructing the cement clinker mineral phase crystal structure model include:
[0024] Firstly, the required crystal structure initial cell cif file is imported into the database, and converted into POSCAR file by VESTA software as input file, and then the structure is optimized to obtain the lattice constants of various clinker crystals;
[0025] Then, the doped Mg, Fe, Al, Zn or W atoms are replaced and then the structure is relaxed;
[0026] Finally, the optimized unit cell is subjected to periodic boundary conditions, and the atoms are statically self-consistent based on density functional theory to obtain a stable configuration.
[0027] Specifically, in step two, obtaining a stable crystal structure by comparing convergence means that the change in total energy is less than 0.01 eV.
[0028] Specifically, the ions in step three include Mg 2+ , Fe 2+ , Al 3+ , Zn 2+ and / or W 2+ .
[0029] Specifically, the static self-consistent calculation steps in step two include:
[0030] Start the calculation, input the initial density ρ0(r), and calculate the effective potential V eff (r);
[0031] Solve the Kohn-Sham equation: (T j +V eff )φ i =ε i φ i ; T j represents the single-electron kinetic energy, φ i is the Kohn-Sham orbital, also known as the single-electron wave function, which describes the spatial distribution and quantum state of the i-th electron in the system, and ε i represents the eigenvalue of the i-th Kohn-Sham orbital, corresponding to the energy of the electron on that orbital;
[0032] Compare the convergence |ρ n+1 -ρ n | < 10 -6 , where ρ represents the electron density, n+1 represents the next iteration, and n represents the number of iterations;
[0033] When the requirements are met, output the result;
[0034] When the requirements are not met, calculate the next input ρ n+1 =F(ρ n ), and jump to the effective potential V eff (r) to continue the operation.
[0035] Specifically, for the possibility of ion doping behavior in step three, the formation energy (E f ) is calculated as follows:
[0036] E f =E T -E0 - n(μ Mg -μ X )
[0037] Where ET and E0 are the total energies of the doped mineral and the original mineral, respectively;
[0038] n is the number of Mg atoms;
[0039] μ Mg and μ X is the chemical potential of Mg and the substituting element X (X = Al, Ca, Fe and Si).
[0040] Specifically, the bond length-bond order distribution in step 4 is used to quantitatively characterize the local structural mismatch, and the value of BO(ραβ) is calculated as follows:
[0041]
[0042] where ρ αβ is a parameter used to measure the strength between a pair of atoms, and its value can be obtained according to the Mulliken scheme; n is the band index; i and j mark the orbital quantum numbers of atoms α and β; C i,α*n and C j,βn is the eigenvector coefficient of the wave function; S iα,jβ is the overlap matrix between the two states; values equal to 0 and 1 represent pure ionic and covalent bonding, respectively.
[0043] Specifically, the charge density calculation in step 4 includes:
[0044] The frontier molecular orbital theory of Fukui function is widely used to predict the chemical reactivity of molecules, clusters and bulk systems; Fukui function can be expressed as:
[0045]
[0046] Where N is the number of electrons, the reactivity of the corresponding position increases with the increase of f(r) under the control of a constant external potential (v(r)) and a differential change of the electron density (ρ(r)) in the system. The function f + (r) (gain electrons) and f - (r) (loss of electrons) is used to estimate the accessibility of nucleophilic and electrophilic attacks, respectively. For bulk materials, f + The (r) and f-(r) functions are approximately equal to the conduction band minimum (CBM), ρCBM(r) and the valence band maximum (VBM), ρVBM(r), respectively. CBM and VBM represent the reaction zones under nucleophilic and electrophilic attacks, respectively.
[0047] Density of states calculation:
[0048] Density of States (DOS) calculation is a commonly used analysis method in condensed matter physics and materials science. It can provide important information about the electronic structure of materials. It is defined as the number of quantum states per unit energy interval. That is, for a system, the density of states g(E) represents the ratio of the number of quantum states dZ with energy between E and E+dE to the energy interval dE. The mathematical expression is:
[0049]
[0050] The density of states can provide information about the distribution of electrons in different energy states. By analyzing the density of states, we can understand the occupation of electrons in the material, the distribution of unoccupied states, and the excited states of electrons. The peak position and width of the density of states can reflect the degree of localization and expansion of the electronic state.
[0051] Based on the first principles, the present invention designs the optimal doping elements, doping positions and concentrations, and incorporates other ions (one or more) into the clinker crystal structure to occupy the sites originally belonging to other ions, forming a solid solution, so as to enhance the activity of the multi-mineral phase structure, increase the strength, and thus optimize the performance of cement clinker.
[0052] The present invention first constructs a cement clinker mineral phase crystal structure model, and performs structural relaxation on the model to obtain a model crystal structure determined by a lattice constant; then, quantum mechanics simulation is used to analyze and optimize the microstructure changes of various mineral phases during the ion doping process and their corresponding energy state changes, and the solid solubility of the doped ions and the mineral phase structure is represented by the defect formation energy of ion doping. The formation energy is negative and the reaction process is a spontaneous process. The closer to 0, the better the solid solubility and the higher the hydration reaction activity, thereby revealing how ion doping enhances its hydration reaction activity and improves its strength. By accurately regulating the characteristics of multi-mineral phase organizations, the mechanical properties, durability and corrosion resistance of cement are improved.
[0053] The present invention is based on first-principles calculations and systematic studies on a method for enhancing the activity of multi-mineral phase structures by ion doping. It is an effective method for improving the performance of cement clinker, can provide an accurate basis for cement design, and is of great significance to the sustainable development of the cement industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 It is a technical flow chart for calculating the properties of mineral crystals of Portland cement clinker by first principles;
[0055] Figure 2 This is a flowchart of static self-consistent calculation in first-principles calculation;
[0056] Figure 3 This is a schematic diagram of the crystal structure of the four main minerals in silicate cement clinker. DETAILED DESCRIPTION
[0057] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0058] First principles calculation, also known as ab initio calculation, is a simulation method based on quantum mechanics that can accurately describe the structure and properties of materials at the atomic level. The application of this method in cement clinker research has the following advantages:
[0059] High-precision prediction: It can accurately predict the effect of ion doping on cement mineral phase, including changes in crystal structure, band structure characteristics and mechanical properties, etc., providing theoretical guidance for subsequent experiments.
[0060] No experimental error: Based on theoretical calculations, the errors caused by experimental operations can be eliminated, making the research results more reliable.
[0061] Opening up new research avenues: Combining first-principles calculations with materials design allows researchers to explore more ion doping combinations, thus opening up new avenues for optimizing cement mineral phases.
[0062] An ion doping method based on first principle calculation comprises the following steps:
[0063] Step 1: construct a cement clinker mineral phase crystal structure model, and perform structural relaxation on the model to obtain a model crystal structure with a determined lattice constant;
[0064] S1.1, select cement clinker mineral phase according to different types of cement, and establish a model using first-principles density functional theory based on its chemical composition and crystal structure characteristics (space group, lattice parameters, etc.) to obtain the crystal structure model of cement clinker mineral phase;
[0065] After the model is built, the constructed model is structurally optimized, i.e., structural relaxation. The clinker structure model is established using MaterialsStudio software as the input file POSCAR required for the structural optimization calculation. Specifically, it includes:
[0066] First, the required crystal structure initial cell cif file, such as M3-C3S, is imported into the software database and converted into a POSCAR file using VESTA software as the input file for structural optimization to obtain the lattice constants of various clinker crystals;
[0067] Then, the doped Mg, Fe, Al, Zn or W atoms are replaced to optimize the structure;
[0068] Finally, the optimized unit cell adopts periodic boundary conditions, and the geometric structure of the atoms is optimized and statically self-consistent based on density functional theory to obtain a stable configuration, thereby preparing the required model for the next step of calculation;
[0069] Structural relaxation refers to the use of the conjugate gradient algorithm with IBRION=2 under periodic boundary conditions and the determination of sufficient relaxation steps to ensure that the system reaches a stable state, perform structural relaxation, generate a CONTCAR file with crystal structure information (lattice parameters), reconvert it to a POSCAR file, and then perform a static self-consistent calculation. The initial density ρ0(r) of the stable crystal structure after structural relaxation is input, and the effective potential V of the stable unit cell is calculated. eff (r) and solve the Kohn-Sham equation, and finally compare the convergence to get the result, so that the various parameters or variables of the structural model reach a stable state, that is, the change in total energy is less than a certain value (0.01eV). In this state, its properties (such as energy, electron density, etc.) reach a balance and no longer change with time.
[0070] S1.2, analyze the doping effects of different ions on cement mineral phases through first principles and quantum mechanics theory, and plan various doping combinations, positions and concentrations;
[0071] Analysis of doping effect:
[0072] First, the doping effects of different ions are clarified, and a group of high-performance ions can be selected for doping based on the calculation of their formation energy and some physical properties. 2+ , Fe 2+ 、Zn 2+ , W 2+ and Al 3+ The doping of ions in cement mineral phase may affect its crystal structure, physical and chemical properties and cement performance. 2+ Ions can improve the corrosion resistance of cement, and Fe 2+ The introduction of ions may enhance the strength and fire resistance of cement. 3+ The addition of iodine helps to improve the setting time and stability of cement.
[0073] Location and combination of doping:
[0074] According to the structural characteristics of cement mineral phase, the doping positions of different ions are planned. 2+ It can be doped in C3S (tricalcium silicate) phase, C2S (dicalcium silicate) or AFm (aluminate phase); and Fe 2+ It is suitable to fill vacancies in the hydration product, Al 3+Doping can be done in the C3A (tricalcium aluminate) phase to improve the hydration activity and strength of cement clinker. Different positions (such as the position of different Ca ions in C3S) may lead to different physical and chemical properties, so it is very important to plan them systematically. In addition, various doping combinations can be designed, such as Mg 2+ With Al 3+ Co-doping or Fe 2+ With Zn 2+ to study their synergistic effects.
[0075] Effect of concentration:
[0076] Doping concentration is also an important factor affecting cement performance. By replacing different atoms in the clinker crystal structure through first-principles calculations, the doping effect of ions at different concentrations is calculated using atomic ratios to determine the optimal doping ratio, thereby optimizing cement performance. For example, too high an ion concentration may cause distortion of the crystal structure, while too low a concentration may not effectively improve cement performance. Therefore, it is necessary to use first-principles calculations to analyze changes in mechanical properties, durability and other indicators of cement mineral phases at different concentrations.
[0077] The cement clinker mineral phases in this case include: tricalcium silicate (C3S), dicalcium silicate (C2S), calcium silicate (CS), calcite (C3S2), tricalcium aluminate (C3A), monocalcium aluminate (CA), monocalcium dialuminate (CA2), dodecaaluminate (C3S), calcium silicate (C3S2), calcium silicate (C3A), calcium aluminate (CA), calcium dialuminate (CA2), calcium silicate (C3S2), calcium silicate (C3S2), calcium silicate (C3A), calcium aluminate (CA), calcium aluminate (CA2), calcium silicate (C3S2), calcium silicate (C3S2), calcium silicate (C3A ...S2), calcium silicate (C3A), calcium silicate (C3A), calcium silicate (C3A), calcium silica 12 A7), dicalcium ferrite (C2F), tetracalcium aluminoferrate (C4AF), hexacalcium aluminoferrate (C6AF2), hexacalcium ferroaluminate (C6A2F), calcium sulfoaluminate (C4A3$), calcium sulfosilicate (C5S2$), calcium barium sulfoaluminate (C3A3$·BaO), calcium strontium aluminate (C3A3$·SrO), calcium fluoroaluminate (C 11 A7·CaF2), calcium chloroaluminate (C 11 A7·CaC12), tricalcium phosphate (C3P), tetracalcium phosphate (C4P), calcium aluminophosphate (C8A4P), P phase (C6A4FS), Q phase (Ca 20 Al 32 -2nMgnSinO 68 ), grosvenite (C2AS) and / or alinite (Ca 22 Si6Al2C12O 36 )wait.
[0078] Each phase has a variety of different structures. Based on the first-principles calculation, the crystal structures (space groups, lattice constants, etc.) of these clinker phases are obtained. Table 1 lists some relevant parameter information of the crystal structures of some clinker phases.
[0079] Table 1 Related parameters of crystal structures of different mineral phases
[0080]
[0081] Step 2: Based on the structural relaxation, the static self-consistent calculation is started by adjusting the VASP calculation, inputting the initial density ρ0(r) of the clinker crystal, calculating its effective potential Veff(r) and solving the Kohn-Sham equation, and finally comparing the convergence to obtain a stable crystal structure;
[0082] Adjusting the VASP calculation refers to two parameters in the input file INCAR;
[0083] INCAR files are automatically generated by the vaspkit plug-in in the VASP software based on the calculation content. In VASP calculations, INCAR files are one of the core input files for calculations. It contains all the calculation parameters and settings, instructing VASP how to perform electronic structure calculations or molecular dynamics simulations.
[0084] The two parameters refer to the IBRION parameter and the NSW parameter in the INCAR file;
[0085] The IBRION parameter is used to specify the algorithm for ion optimization, which controls how to handle the movement of ions in the calculation. In this case, IBRION = -1 is set, which means no ion optimization is performed, that is, the original atomic positions are kept, which is suitable for static self-consistent calculations to obtain the energy and electronic structure of the system.
[0086] The NSW parameter specifies the number of steps for ion optimization. It is used with IBRION to determine the maximum number of ion movement steps allowed during the optimization process. For static calculations, NSW is usually set to 0, which means that no ion movement or optimization steps are performed.
[0087] Density functional theory (DFT) was used to carry out computational simulations. The calculations were performed using the Vienna Ab Initio Package (VASP) in the generalized gradient approximation (GGA). All spin-polarized density functional theory (DFT) calculations were performed using the Perdew-Burke-Ernzerhof (PBE) formula, and the projected enhanced wave (PAW) potential was selected to describe the ion core. The crystal structure changes, bond length and bond order changes, and band structure characteristics after doping were predicted, and the performance impact was evaluated. The specific operations are as follows:
[0088] Static self-consistency includes the following steps:
[0089] Start the calculation, input the initial density ρ0(r), and calculate the effective potential V eff (r);
[0090] Solve the Kohn-Sham equation: (T j +V eff )φ i = ε i v i ; T j represents the single-electron kinetic energy, φ i is the Kohn-Sham orbital, also known as the single-electron wave function, which describes the spatial distribution and quantum state of the i-th electron in the system, and ε i represents the eigenvalue of the i-th Kohn-Sham orbital, corresponding to the energy of the electron in that orbital;
[0091] Compare the convergence |ρ n+1 - ρ n | < 10 -6 , where ρ represents the electron density, n + 1 represents the next iteration, and n represents the number of iterations;
[0092] When the requirements are met, output the result;
[0093] When the requirements are not met, calculate the next input ρ n+1 = F(ρ n ), and jump to the effective potential V eff (r) to continue the calculation;
[0094] Step 3: After the static self-consistent calculation forms a stable crystal structure:
[0095] Step 3.1, calculate the formation energy Ef of atomic substitution in the cement clinker. By substituting different atoms in the clinker with ions, first substituting atoms at different positions represents the doping positions, and secondly substituting different numbers of atoms from less to more represents the doping concentration to obtain the effective formation energy;
[0096] Step 3.2, perform electronic property calculations by calculating the bond length - bond order, density of states, and charge density;
[0097] Step 4: According to the formation energy obtained in 3.1 and the electronic property parameters obtained in 3.2 in Step 3, compare the existence states, doping preferences, and sites of different elements doped in each cement clinker mineral phase crystal to obtain the best doping measures.
[0098] After the static self-consistency, the crystal structures of various clinkers are stable, meeting the requirements for subsequent various electronic property calculations. According to the key performance indicators including cement maturity, strength development, durability, and fluidity, etc., evaluate the performance of the cement clinker through the calculation results of characteristics such as crystal structure changes, bond length - bond order changes, and density of states.
[0099] The formation energy reflects the change in energy during the doping process. The lower the formation energy, the more stable the clinker is during the formation process. That is, the closer its absolute value is to 0, the better the stability.
[0100] The bond length-bond order property can reveal the properties of chemical bonds in cement clinker mineral crystals. Shorter bond lengths and higher bond orders mean stronger chemical bonds. Taking C3S as an example, the bond length and bond order of the Si-O bonds inside it have an important influence on its strength. If the bond length of the Si-O bonds is shorter and the bond order is higher, the breaking and recombination of these chemical bonds will be more orderly and stronger during the cement hydration process. The state density property can reflect the activity of electrons in cement clinker minerals. The higher the electron activity, the higher the reactivity. Charge density is also related to reactivity. For example, the charge density on the surface of doped clinker affects its adsorption capacity for water molecules. A higher charge density can attract more water molecules, accelerate the initiation process of the hydration reaction, and thus increase the reactivity of cement clinker.
[0101] For example: To evaluate Mg 2+ , Fe 2+ 、Al 3+ The possibility of plasma doping behavior, formation energy (E f ) to evaluate it,
[0102] as follows:
[0103] E f =E T -E0-n(μ Mg -μ X )
[0104] Where ET and E0 are the total energies of the doped mineral and the original mineral, respectively;
[0105] n is the number of Mg atoms;
[0106] μ Mg and μ X is the chemical potential of Mg and the substituting element X (X = Al, Ca, Fe and Si).
[0107] Bond length-key sequence calculation:
[0108] The bond order-bond length (BO-BL) distribution is used to quantitatively characterize the local structural mismatch. The value of BO(ραβ) can be calculated as follows:
[0109]
[0110] where ρ αβ is a parameter used to measure the strength between a pair of atoms, and its value can be obtained according to the Mulliken scheme; n is the band index; i and j mark the orbital quantum numbers of atoms α and β; C i,α*nand C j,βn is the eigenvector coefficient of the wave function; S iα,jβ is the overlap matrix between the two states; values equal to 0 and 1 represent pure ionic and covalent bonding, respectively.
[0111] Partial charge density calculation:
[0112] The frontier molecular orbital theory of Fukui function is widely used to predict the chemical reactivity of molecules, clusters and bulk systems; Fukui function can be expressed as:
[0113]
[0114] Where N is the number of electrons, the reactivity of the corresponding position increases with the increase of f(r) under the control of a constant external potential (v(r)) and a differential change of the electron density (ρ(r)) in the system. The function f + f(r) (gain of electrons) and f-(r) (loss of electrons) are used to estimate the accessibility of nucleophilic and electrophilic attacks, respectively. For bulk materials, f + The (r) and f-(r) functions are approximately equal to the conduction band minimum (CBM), ρCBM(r) and the valence band maximum (VBM), ρVBM(r), respectively. CBM and VBM represent the reaction zones under nucleophilic and electrophilic attacks, respectively.
[0115] Density of states calculation:
[0116] Density of States (DOS) calculation is a commonly used analysis method in condensed matter physics and materials science. It can provide important information about the electronic structure of materials. It is defined as the number of quantum states per unit energy interval. That is, for a system, the density of states g(E) represents the ratio of the number of quantum states dZ with energy between E and E+dE to the energy interval dE. The mathematical expression is:
[0117]
[0118] The density of states can provide information about the distribution of electrons in different energy states. By analyzing the density of states, we can understand the occupation of electrons in the material, the distribution of unoccupied states, and the excited states of electrons. The peak position and width of the density of states can reflect the degree of localization and expansion of the electronic state.
[0119] Embodiment 1:
[0120] like Figure 3 As shown, this embodiment uses the first principle to systematically study the doping behavior of manganese ions and zinc ions in the clinker phase:
[0121] The ordinary Portland cement clinker system was selected. First, different clinker model structures were constructed, and then the constructed model was structurally relaxed to obtain the lattice parameters of the clinker. Then, a static self-consistent calculation was performed, and the initial density of the clinker crystal ρ0(r) was input, its effective potential Veff(r) was calculated, and the Kohn-Sham equation was solved. Finally, the convergence was compared to obtain a stable crystal structure. By calculating its energy properties, the stable defect formation energy was obtained, and the co-doping behavior of Mn ions and Zn ions in C3S, C2S, C3A and C4AF mineral phases was analyzed, and the obvious preference of Mn ions and Zn ions to replace Fe ions in C4AF was predicted, as shown in Table 2. The formation energy Ef of atomic substitution in ordinary Portland cement clinker was calculated, and different atoms in the clinker were replaced by Mn ions and Zn ions. Different doping positions and concentrations were analyzed, and the effective formation energy was obtained. The largest solid solution can be formed with the smallest formation energy, and the formation energy obtained by replacing Fe atoms in C4AF with Mn ions and Zn ions is the smallest, the degree of substitution is the highest, and the performance is the best, indicating that the doping of double ions has a great influence on the hydration activity and strength of cement.
[0122] In-depth analysis of the electronic structure shows that the combination Figure 3 It can be clearly seen that both Mn and Zn ions cause local structural distortions, which are reflected in the local bonding structure rather than in global crystal deformation. The bond lengths of those ions far from the defect center remain mainly the same as in the perfect crystal. The local structural distortion depends on the bond order mismatch between Mn-O, Zn-O and XO (X = Si, Ca, Al and Fe), which essentially originates from the difference in electronic structure. Mn ions are present in clinker minerals as Mn 3+ Zn exists stably in the form of Zn 3+ The electronic structure of Fe in C4AF is similar to that of Fe 3+ Very similar, so it is easy to replace each other. The reduction of C3A content caused by Mn and Zn doping is due to the high energy barrier of Mn and Zn incorporation, the chemical bond is strengthened, and the strength of the clinker is increased, because Mn ions and Zn ions do not mainly enter C3A, but react with aluminates according to the minimum energy principle to form brown needle stone crystals. At the same time, according to the calculation results of the density of states (DOS), the charge density of the Mn and Zn ion doped part increases, the number of electrons increases, the electron migration rate is accelerated, and the hydration reaction activity is improved, which has a significant impact on the electronic structure and properties of cement clinker.
[0123] Table 2 Formation energy E calculated by atomic substitution in ordinary Portland cement clinker f .
[0124]
[0125]
[0126] Embodiment 2:
[0127] In this example, the electronic properties of the complex sulphoaluminate cement clinker phase were calculated by density functional theory (DFT) simulation, which can provide direct evidence at the atomic scale to understand the doping behavior of foreign elements. A systematic study was conducted by DFT calculation to determine the exact morphology and doping preference of Mg in the sulphoaluminate cement clinker phase. First, a The main mineral phase crystal structures such as C2S and C4AF were structurally relaxed by VASP to make the crystal structure basically stable, and then the parameters were adjusted for static self-consistency. The initial density ρ0(r) of the crystal after structural optimization was input, and its effective potential Veff(r) was calculated and the Kohn-Sham equation was solved. Finally, the convergence was compared to obtain a stable crystal structure. The element Mg is incorporated into the sulfoaluminate cement clinker phase by forming a substitutional solid solution. The solubility of MgO is about 1.3wt%, and excess Mg is easily accumulated and exists in the form of periclase; as shown in Table 3, the formation energy Ef of atomic substitution in sulfoaluminate cement clinker crystals was calculated. By calculating the formation energy of Mg ions replacing different atoms in different crystals, it is shown that the distribution of Mg covers all areas of the sulfoaluminate cement clinker phase and is distributed in the interstitial phase ( Light enrichment was observed in C4AF and C4AF, where Mg ions simultaneously replaced Fe and S ions, and the minerals C4AF and It shows a stronger ability to accommodate Mg ions than C2S; with the increase of dosage, the large structural mismatch and the sharp increase in formation energy may limit the solubility of Mg in the sulfoaluminate cement clinker phase, thereby affecting the activity of cement hydration. It should be more reasonable to further evaluate the doping possibility of Mg ions on S and Fe from the distribution of bond order-bond length (BO-BL). The more the BO-BL distribution overlaps between the host ion and the guest ion, the higher the possibility of substitution. It can be observed from the BO-BL of SO, Fe-O and Mg-O that the BO-BL distribution of SO is concentrated in a very small area, while that of Fe-O is widely dispersed, ranging from 1.76 to The bond length decreases and the bond order increases, indicating that the Mg-doped clinker has higher strength. There is no overlap in the length distributions of Mg-O and SO. For Mg-O and Fe-O, some values of BO-BL of Mg-O fall within the range of Fe-O, indicating that Mg ions prefer to replace Fe ions in C4AF.
[0128] In addition, another powerful parameter reflecting the bonding efficiency is analyzed by analyzing the electron overlap between different atoms. From its state density, it can be found that the Fe-O bond is mainly contributed by the electron overlap of the 2p orbital of O and the 3d orbital of Mn. Mg-O is mainly contributed by the overlap of the electrons on the 2p orbital of O and the 3d orbital of Mg. From the PDOS distribution of Fe-O and Mg-O, it can be seen that Fe and Mg ions show similar electron contributions. The increase in electrons and the faster electron migration rate accelerate the hydration reaction rate and improve the reaction activity, which plays an important role in determining the doping preference of Mg ions at the Fe site in C4AF. Through calculation, a clear understanding of the existence state of Mg, the doping preference of specific phases, and the exact site provides very important information for guiding the synthesis of sulphoaluminate cement clinker using low-grade high-magnesium limestone.
[0129] Table 3 Formation energy E calculated by atomic substitution in sulphoaluminate cement clinker f
[0130]
[0131] The present invention determines the influence mechanism of multi-ion doping on the activity of multi-mineral phase structure cement materials through a calculation method based on first principles, and reveals the phase change behavior and electronic structure regulation caused by different doping elements at the microstructural level, thereby significantly improving the physical and chemical properties of cement. In addition, studies have shown that multi-solid doping of various ions not only optimizes the distribution of mineral phases and their interactions, but also effectively improves the compressive strength, durability and chemical corrosion resistance of cement, indicating that this method has broad prospects in practical applications. Therefore, the ion doping strategy based on first principles provides a new idea for the development of the cement industry, promotes the research progress of green building materials, and lays a solid foundation for achieving the dual goals of environmental protection and economic benefits.
[0132] Regarding the contents disclosed in this case, there are a few points that need to be explained:
[0133] (1) The drawings of the embodiments disclosed in this case only involve the structures involved in the embodiments disclosed in this case, and other structures can refer to the general design;
[0134] (2) In the absence of conflict, the embodiments and features of the embodiments disclosed in this case can be combined with each other to obtain new embodiments;
[0135] The above are only specific implementation methods disclosed in this case, but the protection scope of the present disclosure is not limited thereto. The protection scope disclosed in this case should be based on the protection scope of the claims.
Claims
1. An ion doping method based on first principle calculation, characterized in that: The following steps are involved: Step 1: construct a cement clinker mineral phase crystal structure model, and perform structural relaxation on the model to obtain a model crystal structure with a determined lattice constant; Step 2: Based on the structural relaxation, the VASP calculation is adjusted to perform a static self-consistent calculation, the initial density ρ0(r) of the clinker crystal is input, its effective potential Veff(r) is calculated, and the Kohn-Sham equation is solved. Finally, the convergence is compared to obtain a stable crystal structure. Step 3: After the static self-consistent calculation forms a stable crystal structure: Step 3.1, calculate the formation energy Ef of atomic substitution in cement clinker, use ions to replace different atoms in the clinker, first replace atoms at different positions to represent the doping position, and then replace different numbers of atoms from small to large to represent the doping concentration, and obtain the effective formation energy; Step 3.2, calculate the electronic properties by calculating the bond length-bond order, state density and charge density; Step 4: Based on the formation energy obtained in 3.1 and the electronic property parameters obtained in 3.2 in step 3, the existence state, doping preference and site of different elements doped in each of the cement clinker mineral phase crystals are compared to obtain the best doping measure.
2. The ion doping method based on first principle calculation according to claim 1, characterized in that: The crystal structure described in step 1 includes: formation energy, bond length and bond order distribution, electronic structure, space group, number of non-bonding electrons, effective charge, local charge density, interplanar spacing and unit cell parameters.
3. The ion doping method based on first principle calculation according to claim 1, characterized in that: The steps for constructing the cement clinker mineral phase crystal structure model include: Firstly, the required crystal structure initial cell cif file is imported into the database, and converted into POSCAR file by VESTA software as input file, and then the structure is optimized to obtain the lattice constants of various clinker crystals; Then, the doped Mg, Fe, Al, Zn or W atoms are replaced and then the structure is relaxed; Finally, the optimized unit cell was subjected to periodic boundary conditions, and the atoms were statically self-consistent based on density functional theory to obtain a stable configuration.
4. The ion doping method based on first principle calculation according to claim 1, characterized in that: Comparing the convergence in step 2 to obtain a stable crystal structure means that the change in total energy is less than 0.01 eV.
5. The ion doping method based on first principle calculation according to claim 1, characterized in that: The ions in step 3 include Mg 2+ , Fe 2+ 、Al 3+ 、Zn 2+ and / or W 2+ .
6. The ion doping method based on first principle calculation according to claim 1, characterized in that: The static self-consistent calculation steps in step 2 include: Start the calculation, input the initial density ρ0(r), and calculate the effective potential V eff (r); Solve the Kohn-Sham equation: (T j +V eff )φ i =ε i φ i ; T j represents the kinetic energy of a single electron, φ i is the Kohn-Sham orbital, also known as the single electron wave function, which describes the spatial distribution and quantum state of the i-th electron in the system, ε i represents the eigenvalue of the i-th Kohn-Sham orbital, corresponding to the energy of the electron in this orbital; Comparing Convergence | ρ n+1 -ρ n | < 10 -6 , where ρ represents the electron density, n + 1 represents the next iteration, and n represents the number of iterations; When the requirements are met, output the results; When it does not meet the requirements, calculate the next step input ρ n+1 =F(ρ n ), jump to the effective potential V eff (r) Continue to calculate.
7. The ion doping method based on first-principles calculation according to claim 1, characterized in that: The possibility of ion doping behavior in step 3, the formation energy (Ef) is calculated as follows: BY f =E T -E0-n(μ Mg -μ X ) Where ET and E0 are the total energies of the doped mineral and the original mineral, respectively; n is the number of Mg atoms; μ Mg and μ X is the chemical potential of Mg and the substituting element X (X = Al, Ca, Fe and Si).
8. The ion doping method based on first principle calculation according to claim 1, characterized in that: In step 4, the bond length-bond order distribution is used to quantitatively characterize the local structural mismatch, and the value of BO(ραβ) is calculated as follows: where ρ αβ is a parameter used to measure the strength between a pair of atoms, and its value can be obtained according to the Mulliken scheme; n is the band index; i and j mark the orbital quantum numbers of atoms α and β; C i,α*n and C j,βn is the eigenvector coefficient of the wave function; S iα,jβ is the overlap matrix between the two states; values equal to 0 and 1 represent pure ionic and covalent bonding, respectively.
9. The ion doping method based on first principle calculation according to claim 1, characterized in that: The charge density calculation in step 4 includes: The frontier molecular orbital theory of Fukui function is widely used to predict the chemical reactivity of molecules, clusters and bulk systems; Fukui function can be expressed as: Where N is the number of electrons, the reactivity of the corresponding position increases with the increase of f(r) under the control of a constant external potential (v(r)) and a differential change of the electron density (ρ(r)) in the system. The function f + (r) (gain electrons) and f - (r) (loss of electrons) is used to estimate the accessibility of nucleophilic and electrophilic attacks, respectively. For bulk materials, f + (r) and f - The (r) function is approximately equal to the conduction band minimum (CBM), ρCBM(r) and the valence band maximum (VBM), ρVBM(r), respectively. CBM and VBM represent the reaction zones under nucleophilic and electrophilic attacks, respectively.
10. Application of the ion doping method based on first principle calculation as claimed in claim 1 in cement clinker design.
Citation Information
Cited By
MOFs material structure performance analysis method, storage medium and electronic equipment
CN120089259A
Sodium fluosilicate production optimization calculation method
CN122117181A